2015
DOI: 10.5603/cj.a2014.0025
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between P wave dispersion, atrial electromechanical delay, left atrial remodeling, and NT-proBNP levels, in patients with hypertrophic cardiomyopathy

Abstract: Background: We evaluated the associations among the well-known atrial fibrillation (AF) predictors including P-wave dispersion (PWD), intra-and inter-atrial electromechanical dyssynchrony (EMD), left atrial (LA) phasic functions, and plasma N-terminal prohormone of B-type natriuretic peptide (NT-proBNP) levels, in patients with hypertrophic cardiomyopathy (HCM p = 0.001), p = 0.03), p = 0.006), but not, however, to LAAEFr (p = 0.4). The plasma NT-proBNP levels of patients were not correlated with either (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 29 publications
2
11
0
Order By: Relevance
“…Our data support that structural remodeling in the LA of HCM patients causes heterogeneity in propagation of atrial impulses which leads to vulnerability to atrial reentry as previously speculated . We previously showed that prolonged PWD was related to impaired LA reservoir functions in HCM . We entered PWD and LA phasic functions in a multivariate analysis which showed that the structural impairment of LA does not only play a role in AF development but also electrical LA remodeling observed in the disease spectrum may have a role in promoting AF.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Our data support that structural remodeling in the LA of HCM patients causes heterogeneity in propagation of atrial impulses which leads to vulnerability to atrial reentry as previously speculated . We previously showed that prolonged PWD was related to impaired LA reservoir functions in HCM . We entered PWD and LA phasic functions in a multivariate analysis which showed that the structural impairment of LA does not only play a role in AF development but also electrical LA remodeling observed in the disease spectrum may have a role in promoting AF.…”
Section: Discussionsupporting
confidence: 89%
“…P‐wave dispersion was calculated as previously described . Briefly, a 12‐lead resting surface ECG was obtained from all patients (lying supine) at a paper speed of 50 mm/sec and a signal size of 20 mm/mV, during SR, using a computer‐based ECG system.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations